Pathogenesis II: Fungal responses to host responses: Interaction of host cells with fungi - Mendes-Giannini, Maria José Soares [UNESP]; Taylor, M. L.; Bouchara, J. B.; Burger, E.; Calich, V. L.G.; Escalante, E. D.; Hanna, S. A. [UNESP]; Lenzi, H. L.; Machado, M. P.; Miyaji, M.; da Silva, J. L. Monteiro [UNESP]; Mota, E. M.; et al. (My University, 2000)
Most of our knowledge concerning the virulence determinants of pathogenic fungi comes from the infected host, mainly from animal models and more recently from in vitro studies with cell cultures. The fungi usually present intra- and/or extracellular host-parasite interfaces, with the parasitism phenomenon dependent on complementary surface molecules. Among living organisms, this has been characterized as a cohabitation event, where the fungus is able to recognize specific host tissues acting as an attractant, creating stable conditions for its survival. Several fungi pathogenic for humans and animals have evolved special strategies to deliver elements to their cellular targets that may be relevant to their pathogenicity. Most of these pathogens express surface factors that mediate binding to host cells either directly or indirectly, in the latter case binding to host adhesion components such as extracellular matrix (ECM) proteins, which act as 'interlinking' molecules. The entry of the pathogen into the host cell is initiated by fungal adherence to the cell surface, which generates an uptake signal that may induce its cytoplasmic internalization. Once this is accomplished, some fungi are able to alter the host cytoskeletal architecture, as manifested by a rearrangement of microtubule and microfilament proteins, and this can also induce epithelial host cells to become apoptotic. It is possible that fungal pathogens induce modulation of different host cell pathways in order to evade host defences and to foster their own proliferation. For a number of pathogens, the ability to bind ECM glycoproteins, the capability of internalization and the induction of apoptosis are considered important factors in virulence. Furthermore, specific recognition between fungal parasites and their host cell targets may be mediated by the interaction of carbohydrate-binding proteins, e.g., lectins on the surface of one type of cell, probably a parasite, that combine with complementary sugars on the surface of host-cell. These interactions supply precise models to study putative adhesins and receptor-containing molecules in the context of the fungus-host interface. The recognition of the host molecules by fungi such as Aspergillus fumigatus, Paracoccidioides brasiliensis and Histoplasma capsulatum, and their molecular mechanisms of adhesion and invasion, are reviewed in this paper. © Oxford University Press 2001.
Keywords: Aspergillus fumigatus; Fungus interaction; Histoplasma capsulatum; Paracoccidioides trasiliensis